Characterization of Livestock-Associated Methicillin-Resistant Staphylococcus aureus Isolates Obtained From Commercial Rabbitries Located in the Iberian Peninsula - Moreno-Grúa, Elena; Pérez-Fuentes, Sara; Muñoz-Silvestre, Asunción; Viana, David; Fernández-Ros, Ana B.; Sanz-Tejero, Celia; Corpa, Juan M.; Selva, Laura (Frontiers in Microbiology, 2018)
Infections caused by methicillin-resistant Staphylococcus aureus (MRSA) have been a growing problem in human medicine since the 1960s, and more recently in veterinary medicine with the appearance of livestock-associated MRSA (LA-MRSA). Nevertheless, information about the presence of MRSA in rabbits is quite scarce since only one LA-MRSA identification has been previously reported. The present study aimed to determine genotypic characterization by verifying the presence of resistance determinants, virulence and toxin genes of different S. aureus strains that cause lesions in rabbits, and their phenotypic traits based on the antimicrobial susceptibility profile. The analysis of 240 S. aureus isolates obtained from different lesion types collected from 89 Spanish and Portuguese rabbit commercial farms in the last four years (2014-2017) was performed. The methicillin-resistant gene mecA was found in 11.25% of the studied isolates (27 of 240) from 19 farms (13 Spanish and 6 Portuguese). Staphylococcal cassette chromosome mec (SCCmec) typing predominantly revealed type III (n=15). Additionally, three MRSA isolates carrying the mecC gen were detected in samples from 3 different farms (2 Spanish and 1 Portuguese). None of the 30 MRSA isolates was PVL-positive or tst-positive. After the MLST procedure, 16 belonged to ST2855, six to ST146, six to ST398 and two ST4774. No ST121 isolate was mec-positive. ST398 and ST4774 isolates lacked the immune-evasion-cluster (IEC) genes. ST2855 strains were associated with the presence only of the sak gene, and ST146 isolates were ascribed to IEC type E. Therefore, this is the first description of LA-MRSA from rabbits belonging to ST2855. Interestingly, one ST2855 and two ST4774 isolates were mecC-positive, which could act as a mecC-MRSA reservoir. More studies are needed to further characterize these isolates and their relationship with humans and other animal species.